Ré-écrire le voyage. La fonction de l’intertextualité dans les récits de voyage à Majorque au XIXe siècle - Isabelle Bes Hoghton (Çédille: Revista de Estudios Franceses, 2013)
We analyze in this article the function of intertextuality in the writings of French travellers to Majorca in the XIXth century. Travel writings are rife with citations, refer-ences and allusions. All these strategies display a very specific narrative function within the text that encapsulates them, ranging from the referential function, the argumentative function, the poetic function, the expressive function and, finally, the critical function.